Computer Network Design Using PPDIOO Method With Case Study of SMA Negeri 1 Kunir - Yuliana, Dela; Mogi, I Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
Technological developments are very beneficial for the world of education, such as the use of the internet in finding and managing information and can help in the teaching and learning process. Before using the internet, there was a computer network that played an important role in it. In building a computer network, a concept or method is needed in designing it, and here the PPDIOO method will be used and uses two types of network topologies, namely star and ring topologies. With the design of this computer network, it can help schools in the teaching and learning process and can improve the quality of teaching, the quality of knowledge and the quality of the abilities of students and teachers. Keywords : Education, Technology, Computer Networks, PPDIOO Method, Network Topology